2014
DOI: 10.1167/iovs.13-13520
|View full text |Cite
|
Sign up to set email alerts
|

Visually Impaired Drivers Who Use Bioptic Telescopes: Self-Assessed Driving Skills and Agreement With On-Road Driving Evaluation

Abstract: Bioptic drivers show insight into the overall quality of their driving and areas in which they experience driving difficulty. They report using the bioptic telescope while driving, contrary to previous claims that it is primarily used to pass the vision screening test at licensure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 19 publications
3
30
3
Order By: Relevance
“…13,19 In Owsley's recent investigation, the majority of a sample reported using their device to improve driving performance, contrary to this proposed belief. 2 Likewise, in a previous study, it was noted that more than half of the bioptic drivers observed were frequently utilising the telescope for spotting while driving. 19 Recent investigations seem to emphasise the importance of assessing the comprehensive individual in regards to not only their visual function but also their visual processing, cognitive, and motor functions.…”
Section: The Bioptic Controversymentioning
confidence: 89%
See 4 more Smart Citations
“…13,19 In Owsley's recent investigation, the majority of a sample reported using their device to improve driving performance, contrary to this proposed belief. 2 Likewise, in a previous study, it was noted that more than half of the bioptic drivers observed were frequently utilising the telescope for spotting while driving. 19 Recent investigations seem to emphasise the importance of assessing the comprehensive individual in regards to not only their visual function but also their visual processing, cognitive, and motor functions.…”
Section: The Bioptic Controversymentioning
confidence: 89%
“…14 The evidence regarding the safety and efficacy of bioptic use is still unclear, as some controlled studies show its advantages whereas others elucidate its challenges. 2,12,15,16 Specifically, one study involving bioptic drivers in Massachusetts 17 suggested that they were safe drivers when compared with the general population, whereas another study presented some concerns in Texas. 18 Owsley points out that some of these studies are dated, have limitations in research design, and did not involve training programs with updated technological advances.…”
Section: The Bioptic Controversymentioning
confidence: 99%
See 3 more Smart Citations